Gender Dan Sistem Kekerabatan Matrilinial - Esli Zuraidah Siregar; Ali Amran (Jurnal Kajian Gender dan Anak, 2020)
Matrilinial is one of the oldest kinship systems found in Indonesia, and the world. This system adheres to kinship systems and inheritance systems from the maternal lineage. in the matrilinial kinship system, women have a special place and play a significant role in their community compared to women who adhere to the patrilinieal system. In the matrilineal kinship system, men and women have their respective obligations and responsibilities according to their gender. In this case they have a balanced position, namely men occupying positions as supervisors and protectors who are given an honorable position as mamak (mother's brother), while women have access as ownership. In a sense, women get privileged places, and men become powerful figures. However, in making decisions, men and women have the same position